2022
DOI: 10.1044/2021_aja-20-00196
|View full text |Cite
|
Sign up to set email alerts
|

Noise Exposure and Use of Hearing Protection Among Adolescents in Rural Areas

Abstract: Purpose: Noise-induced hearing loss (NIHL) has been found in rural children, potentially due to occupational and recreational noise exposure without consistent use of hearing protection devices (HPDs). However, questions remain regarding the specifics of rural adolescents' noise exposure and use of hearing protection around different types of noise. As such, the purpose of the current study was to provide preliminary results on rural adolescents' noise exposure and use of hearing protection for gun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…The clinical questionnaire was designed by the authors based on previously reported risk factors for hearing loss. 410 43 45 The clinical questionnaire included questions about childbirth mode (caesarean vs vaginal delivery); breast feeding in infancy (yes/no); moderate alcohol consumption (defined as more than two times a week: consumption of two drinks per day of one beer (350 mL, 4.5% alcohol) or one glass of wine (148 mL, 12%–16% alcohol) or more than two shots of Colombian schnapps (90 mL, 30% alcohol)); 46 cigarette smoking (more than 1–5 days per month); 43 high volume use of recreational headphones or personal devices for more than 2 hours per day; 44 duration of recreational headphones or personal devices in hours; 44 number of times attending ‘picó’ (a social gathering event that exceeds 120 dB (A)); number of times attending a bar/pub/disco in the last month; exposure to loud environmental noises at home (traffic, building constructions near home); number of hours of exposure to high volumes of noise; 45 prior self-reported hearing difficulties or hearing loss; previous hearing loss-related noises: ringing, whistling, clicking, roaring (tinnitus); 47 constantly telling people to repeat messages or to speak louder to understand what they say; concentration difficulties due to noise. 48 Finally, height and weight were directly measured by the medical doctors following clinical guidelines to ensure the accuracy and reliability of childhood growth measurement equipment and using previously calibrated weights and rods.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical questionnaire was designed by the authors based on previously reported risk factors for hearing loss. 410 43 45 The clinical questionnaire included questions about childbirth mode (caesarean vs vaginal delivery); breast feeding in infancy (yes/no); moderate alcohol consumption (defined as more than two times a week: consumption of two drinks per day of one beer (350 mL, 4.5% alcohol) or one glass of wine (148 mL, 12%–16% alcohol) or more than two shots of Colombian schnapps (90 mL, 30% alcohol)); 46 cigarette smoking (more than 1–5 days per month); 43 high volume use of recreational headphones or personal devices for more than 2 hours per day; 44 duration of recreational headphones or personal devices in hours; 44 number of times attending ‘picó’ (a social gathering event that exceeds 120 dB (A)); number of times attending a bar/pub/disco in the last month; exposure to loud environmental noises at home (traffic, building constructions near home); number of hours of exposure to high volumes of noise; 45 prior self-reported hearing difficulties or hearing loss; previous hearing loss-related noises: ringing, whistling, clicking, roaring (tinnitus); 47 constantly telling people to repeat messages or to speak louder to understand what they say; concentration difficulties due to noise. 48 Finally, height and weight were directly measured by the medical doctors following clinical guidelines to ensure the accuracy and reliability of childhood growth measurement equipment and using previously calibrated weights and rods.…”
Section: Methodsmentioning
confidence: 99%